Developing a Peer Counseling Guidebook for Junior High School Students: Enhancing Counseling Services and Promoting Mental Well-being - Rohayati, Rohayati; Emosda , Emosda; Jamilah, Jamilah (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2022)
The development of a peer counseling guidebook for junior high school students aims to enhance the quality of counseling services in schools. Drawing from the necessity of addressing adolescent challenges and the significance of peer influence, this study utilized a development model to create an effective guide. The research involved 42 class VIII students, following the ADDIE model for guide development. Material and design experts validated the guide, resulting in high scores of 96.8% and 87.5%, respectively. Field trials exhibited promising results, with an average score of 85.7% to 90.3%. The guidebook's potential was evident in positive student responses, indicating its capacity to strengthen social support networks and promote mental well-being among adolescents. This research contributes a holistic approach to guidebook development, emphasizing practical needs and mental health literacy. Despite limitations in generalizability, future research should broaden field trials to diverse school contexts for wider applicability. In conclusion, the peer counseling guide offers valuable support in addressing adolescent challenges, emphasizing the importance of peer influence in school counseling services.